2022
DOI: 10.3390/ijms232113518
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of StSRO Gene Family and Its Expression in Response to Different Abiotic Stresses in Potato

Abstract: As a highly conserved family of plant-specific proteins, SIMILAR-TO-RCD-ONE (SROs) play an essential role in plant growth, development and response to abiotic stresses. In this study, six StSRO genes were identified by searching the PARP, RST and WWE domains based on the genome-wide data of potato database DM v6.1, and they were named StSRO1–6 according to their locations on chromosomes. StSRO genes were comprehensively analyzed using bioinformatics methods. The results showed that six StSRO genes were irregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 63 publications
(116 reference statements)
1
4
0
Order By: Relevance
“…Phylogenetic analyses with different plant SROs revealed that the 86 SRO members of the abovementioned six Brassica species could be categorized into four subgroups, and members within the same subgroup presented similar gene structures and conserved motif compositions. This phenomenon has also been found in other plant SROs studies as well as in other gene family identifications, 18 , 19 , 41 , 42 further demonstrating their close evolutionary relationship. In addition, our evolutionary tree results showed that, with the exception of individual members, the SROs of monocotyledonous and dicotyledonous plants were in separate subgroups.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Phylogenetic analyses with different plant SROs revealed that the 86 SRO members of the abovementioned six Brassica species could be categorized into four subgroups, and members within the same subgroup presented similar gene structures and conserved motif compositions. This phenomenon has also been found in other plant SROs studies as well as in other gene family identifications, 18 , 19 , 41 , 42 further demonstrating their close evolutionary relationship. In addition, our evolutionary tree results showed that, with the exception of individual members, the SROs of monocotyledonous and dicotyledonous plants were in separate subgroups.…”
Section: Discussionsupporting
confidence: 81%
“…However, although different members presented diverse response expression patterns, none of them showed regular changes. This phenomenon has been found in studies of other plant SROs , such as those of rice, 6 maize, 14 poplar, 22 tea plant, 21 potato 18 and tomato, 16 and has also been presented in the analysis of other gene families. This might be related to the different regulatory mechanisms they were subjected to during the different treatment periods.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations